2020
DOI: 10.3233/adr-200170
|View full text |Cite
|
Sign up to set email alerts
|

Gliosis Precedes Amyloid-β Deposition and Pathological Tau Accumulation in the Neuronal Cell Cycle Re-Entry Mouse Model of Alzheimer’s Disease

Abstract: Background: The presence of cell cycle markers in postmortem Alzheimer’s disease (AD) brains suggest a potential role of cell cycle activation in AD. It was shown that cell cycle activation in postmitotic neurons in mice produces Aβ and tau pathologies from endogenous mouse proteins in the absence of AβPP or tau mutations. Objective: In this study, we examined the microglial and astrocytic responses in these mice since neuroinflammation is another key pathological featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…Forced cell cycle re-entry in neurons results in classical hallmarks of AD, including tau protein hyperphosphorylation and neurofibrillary tangles (NFT), increased APP processing and extracellular deposits of Aβ, neuronal cell death, gliosis, and cognitive deficits [69][70][71][72], and it has been shown to enhance the phenotype of a murine model of AD [73]. Musi et al [74] have recently shown that genes involved in cell cycle progression are upregulated in human NFTcontaining neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Forced cell cycle re-entry in neurons results in classical hallmarks of AD, including tau protein hyperphosphorylation and neurofibrillary tangles (NFT), increased APP processing and extracellular deposits of Aβ, neuronal cell death, gliosis, and cognitive deficits [69][70][71][72], and it has been shown to enhance the phenotype of a murine model of AD [73]. Musi et al [74] have recently shown that genes involved in cell cycle progression are upregulated in human NFTcontaining neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Tau is the major neuronal microtubule associated protein. In the brain of AD patients, tau is abnormally hyperphosphorylated, accumulating as intraneuronal tangles and failing to maintain structures [ 43 ], causing cell apoptosis [ 44 , 45 , 46 ]. Thus, pharmacologic strategies designed to suppress hyperphosphorylation of tau may be beneficial for the treatment of AD.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between neuronal cell cycle re-entry and various AD pathologies has been demonstrated in various models. Connections have been made between neuronal cell cycle re-entry and A␤ pathology [25,32], tau dysfunction [25,[33][34][35], neuroinflammation [24,26,36,37], and neuronal loss [24,25,33]. Of these models, our Simian Virus 40 Large T (SV40T)-mediated neuronal cell cycle re-entry mouse model is the only one shown to simultaneously display the greatest number of pathologies associated with AD [24,26].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of SV40T is targeted to excitatory forebrain neurons by crossing the TAg mice with Camk2a-tTA Tg mice that express tetracycline-controlled transactivator (tTA) under the control of the CamKinase II␣ (Camk2a) promoter (Camk2a-tTA, or "OFF" mice) [50]. Mice expressing both "TAg" and "OFF" undergo neuronal cell cycle re-entry once doxycycline is removed from the diet, typically at one month of age [25,37]. And this neuronal cell cycle re-entry is abolished when the animals are put back on dox diet to suppress SV40T expression [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation